Reliability of ultrasonography and the Alvarado scoring system in acute appendicitis - Ahmet Sami Yazar; Seher Erdoğan; Ceyhan Şahin; Şirin Güven (The Turkish Journal of Pediatrics)
In this study, we aimed to evaluate the diagnostic performance of ultrasonography, the Alvarado score, mean platelet volume and C-reactive protein in the diagnosis of acute appendicitis. Patients admitted to the pediatric emergency department with abdominal pain who were operated on with a preliminary diagnosis of acute appendicitis were evaluated. The patients who had acute appendicitis diagnosis in the histopathological assessment were considered as the Appendicitis (App) Group, while patients who did not have acute appendicitis according to histopathology were considered as the Non-app Group. Of 200 patients assessed in the study, 137 (68.5%) were male and 63 (31.5%) were female. Of the patients operated on; 170 (85%) had acute appendicitis, while the pathological results of 30 (15%) were not consistent with acute appendicitis. The Alvarado score of the patients in App Group was significantly higher than those in Non-app Group (p=0.001). The sensitivity and specificity of the Alvarado score and ultrasonography were 60%, 81.18% and respectively, for the diagnosis of appendicitis. There were no significant differences (p > 0.05) in terms of average white blood cell, absolute neutrophil count, platelet count, mean platelet volume and C-reactive protein between the two groups. According to our study the use of Alvarado Scoring System with ultrasonography is more effective and accurative than ultrasonography performing alone. We recommend performing ultrasonography on patients with right lower quadrant pain and suspected appendicitis admitted to the emergency department and to operate on patients with a ultrasonography-supported appendicitis diagnosis and an Alvarado score of 7 and above. Patients with an appendicitis diagnosis not supported by ultrasonography and an Alvarado score lower than 7 should be closely monitored.